Bullying in UK cardiology: a systemic problem requiring systemic solutions. Issue 3 (6th December 2021) - Camm, Christian Fielder; Joshi, Abhishek; Moore, Abigail; Sinclair, Hannah C; Westwood, Mark; Greenwood, John Pierre; Calver, Alison; Ray, Simon; Allen, Christopher
Abstract : Objectives: Bullying of trainee doctors has been shown to be associated with detrimental outcomes for both doctors and patients. However, there is limited evidence regarding the level of bullying of trainees within medical specialties. Methods: An annual survey of UK cardiology trainees was conducted through the British Junior Cardiologists' Association between 2017 and 2020 and asked questions about experiencing and witnessing bullying, and exposure to inappropriate language/behaviour in cardiology departments. Fisher's exact tests and univariable logistic regression models were used to describe associations between trainee characteristics, and reports of bullying and inappropriate language/behaviour. Results: Of 1358 trainees, bullying was reported by 152 (11%). Women had 55% higher odds of reporting being bullied (OR: 1.55 95% CI (1.08 to 2.21)). Non-UK medical school graduates were substantially more likely to be bullied (European Economic Area (EEA) OR: 2.22 (1.31 to 3.76), non-EEA/UK OR: 3.16 (2.13 to 4.68)) compared with those graduating from UK-based medical schools. Women were more likely than men to report sexist language (14% vs 4%, p<0.001). Non-UK medical school graduates were more likely to experience racist language (UK 1.5%, EEA 6%, other locations 7%, p=0.006). One-third of trainees (33%) reported at least one inappropriate behaviour with 8% reporting being shouted at or targeted with spontaneous anger. Consultants in cardiology (82%) and other specialties (70%) were most commonly implicated by those reporting bullying. Discussion: Bullying and inappropriate language are commonly experienced by cardiology trainees and disproportionately affect women and those who attended non-UK medical schools. Consultants both in cardiology and other specialties are the most commonly reported perpetrators.